2017
DOI: 10.15252/emmm.201607176
|View full text |Cite
|
Sign up to set email alerts
|

Administration of RANKL boosts thymic regeneration upon bone marrow transplantation

Abstract: Cytoablative treatments lead to severe damages on thymic epithelial cells (TECs), which result in delayed de novo thymopoiesis and a prolonged period of T‐cell immunodeficiency. Understanding the mechanisms that govern thymic regeneration is of paramount interest for the recovery of a functional immune system notably after bone marrow transplantation (BMT). Here, we show that RANK ligand (RANKL) is upregulated in CD4+ thymocytes and lymphoid tissue inducer (LTi) cells during the early phase of thymic regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 72 publications
2
63
0
Order By: Relevance
“…29,108 Notably, however, the success of these approaches often requires a significant lag time, whereas an intrathymic AAV gene strategy corrected the medullary microenvironment within less than 10 days, which is concomitant with a correction in T-cell deficiency and differentiation of SP4 thymocytes. It will be of interest to determine whether a combined approach, concomitantly correcting a T-cell deficiency and the medullary microenvironment, 59 further promotes reconstitution. Furthermore, AAV can be used to deliver TEC-inducing molecules to patients with suboptimal T-cell differentiation (eg, boosting thymocyte differentiation in HSC-transplanted patients with cancer by means of intrathymic AAV administration of the IL-22 cytokine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,108 Notably, however, the success of these approaches often requires a significant lag time, whereas an intrathymic AAV gene strategy corrected the medullary microenvironment within less than 10 days, which is concomitant with a correction in T-cell deficiency and differentiation of SP4 thymocytes. It will be of interest to determine whether a combined approach, concomitantly correcting a T-cell deficiency and the medullary microenvironment, 59 further promotes reconstitution. Furthermore, AAV can be used to deliver TEC-inducing molecules to patients with suboptimal T-cell differentiation (eg, boosting thymocyte differentiation in HSC-transplanted patients with cancer by means of intrathymic AAV administration of the IL-22 cytokine).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell reconstitution was monitored by using flow cytometry, and frozen thymic sections were stained, as previously described. 59 Vector genomes were monitored by using real-time PCR. For integration analyses, we adopted a sonication-based linker-mediated PCR method, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that in this study, following TBI, LTi/ILC3 cells also upregulated RANKL expression, a molecule which has since been implicated in thymus regeneration. In another study (99), and following irradiation of WT mice, CD45 + cells upregulated RANKL expression compared to non-irradiated controls. Further analysis showed that RANKL expression was upregulated by radioresistant host LTi/ILC3 and CD4 + cells.…”
Section: Approaches To Enhance Thymus Recovery Il22 and Bmp4mentioning
confidence: 93%
“…Interestingly, and perhaps in line with the potential importance of additional TNF Receptor superfamily members in thymus regeneration, a role for lymphotoxin signaling was also suggested, as stimulation by RANKL caused induction of LTα expression by LTi/ILC3 cells. Moreover, LTα deficient mice had reduced TEC recovery post-BMT compared to WT hosts, suggesting a mechanism of TEC recovery via LTα upregulation mediated by RANKL (99).…”
Section: Approaches To Enhance Thymus Recovery Il22 and Bmp4mentioning
confidence: 97%
“…Recent data in mouse models of allogeneic transplantation have also established the role of interleukin‐22 (IL‐22) and RankL/lymphotoxin α signaling provided by innate cell populations such as lymphoid tissue inducer cells in the regeneration of the thymic microenvironment and T‐cell differentiation following thymic epithelial damage. Interestingly, exogenous administration of RankL was effective independently of age, making it also potentially applicable for older patients . The clinical impact of these factors has yet to be determined, especially in light of the potential side effects such as osteoporosis in the case of RankL .…”
Section: Stimulating Thymic Regeneration and T‐cell Output Post‐transmentioning
confidence: 99%